A REVIEW OF THE IMPLEMENTATION OF EXPERIENTIAL LEARNING COURSES - Burac Jr., Rodolfo B.; B. Espinosa Sr, Emilio (International Journal of Psychosocial Rehabilitation, 2020)
This quantitative study dealt with the implementation of the Experiential Learning Courses. It aimed to measure the intended learning outcomes and the level of engagement, the challenges and benefits derived in the implementation of Field Study Courses. A 5-point Likert scale was used to measure the intended outcomes and the level of engagement of the respondents. The results show that the level of the intended learning outcomes measured was interpreted as very much achieved, and the level of participation of all the respondents was interpreted as very much participated. The results show that when experiential learning is implemented according to its processes, the intended learning outcome will be achieved. Further, the results imply that even if there are challenges in the implementation of the field study courses, the overall implementation is still successful.